The Efficiency of State Aid for the Deployment of High-Speed Broadband: Evidence from the French Markets - Marc Bourreau; Lukasz Grzybowski; Ángela Mu\~noz-Acevedo (Center for Economic Studies and ifo Institute (CESifo), 2023)
In this paper, we evaluate the efficiency of the French State aid plan for broadband deployment, the Plan France Très Haut Débit. According to State aid rules, public subsidies should not be substitute for private investment and should target areas with market failures. We estimate a structural model of fiber entry using a rich dataset on fiber deployment for more than 34,000 municipalities in mainland France over 2014-2019. We then assess whether private investment would have occurred in subsidized municipalities in the absence of public subsidies. We find that between 64% and 93% of the time, public subsidies were granted to municipalities where private entry would not have occurred. Overall, we estimate the cost of "inefficient" public subsidies to be between 243 and 902 million euros, with total subsidies amounting to 2,203 million euros by the end of 2019. Finally, we find that the plan helped to increase fiber coverage in subsidized municipalities in the early stages of fiber deployment.
Keywords: D22; L10; L40; L33; L96; H44; 330; state aid; ex-post evaluation; broadband; entry; coverage; crowding out